Histological Effects of Intravitreal Injection of Antifungal Agents in New Zealand White Rabbits: An Electron Microscopic and Immunohistochemical Study - Sofia Karachrysafi; Antonia Sioga; Anastasia Komnenou; Athanasios Karamitsos; Maria Xioteli; Ioanna Dori; Georgios Delis; Evangelia Kofidou; Penelope Anastasiadou; Sotiris Sotiriou; Vasileios Karampatakis; Theodora Papamitsou (MDPI AG, 2020)
Fungal endophthalmitis is a serious and vision-threatening infection which requires an immediate and effective treatment approach. Our research aims to elucidate the histological effects of the intravitreal injection of the maximum safe dosage of voriconazole and micafungin on retina. Six albino New Zealand White Rabbits were used. In experimental animals, a solution of voriconazole (Group V) or micafungin (Group M) was intravitreally injected in the right eye, while in control animals, balanced salt solution was intravitreally injected in the left eye (Group C). Euthanasia was performed ten days post injection and the retina was removed and prepared for histological examination with a light and electron microscope. Eosin-hematoxylin staining did not reveal any pathological changes in any of the samples examined. The immunohistochemical staining for Tumor Necrosis Factor alpha (TNF-a) marker was detected as negative in all samples, while Interleukin 6 (IL-6) marker was detected as mild only in the group injected with voriconazole. Electron microscopy revealed several ultrastructural alterations in retinal layers in both groups of experimental animals. Histological retinal lesions, revealed with electron microscopy in the present investigation, raises the question of the safe usage of these antifungal agents in the treatment of fungal intraocular infections in the future.